An Alternative to Clay in Building Materials: Red Mud Sintering Using Fly Ash via Taguchi’s Methodology - Suchita Rai; Dilip H. Lataye; M. J. Chaddha; R. S. Mishra; P. Mahendiran; J. Mukhopadhyay; ChangKyoo Yoo; Kailas L. Wasewar (Advances in Materials Science and Engineering, 2013)
“Red mud” or “bauxite residue” is a highly alkaline waste generated from alumina refinery with a pH of 10.5–12.5 which poses serious environmental problems. Neutralization or its treatment by sintering in presence of additives is one of the methods for overcoming the caustic problem as it fixes nearly all the leachable free caustic soda present in red mud. In the present study, feasibility of reducing the alkaline nature of red mud by sintering using fly ash as an additive via Taguchi methodology and its use for brick production, as an alternative to clay, is investigated. The analysis of variance (ANOVA) shows that sintering temperature is the most significant parameter in the process. A pH of 8.9 was obtained at 25–50% of red mud and 50–75% fly ash with water and temperature of . Alternatively 50% of red mud can be mixed with 50% of fly ash with water at temperature of to get a pH of about 8.4. The mechanism of this process has been explained with also emphasis on chemical, mineralogical, and morphological analysis of the sintered red mud. The results would be extremely useful in utilization of red mud in building and construction industry.